Motocross madness - Dixon, Franklin W. (New York : Aladdin Paperbacks, 2005)
The Hardy Boys and their friend Jamal are participating in a motorcycle exhibition and some criminals are trying to ruin it so the Hardy Boys are trying to find the criminals. Frank and Joe get revved up to race for their lives! The Hardy boys and their friend Jamal are thrilled to be participating in a motorcycle exhibition. It's going to be an exciting weekend, with many talented cyclists heating up the competition and a valuable prize for the winner -- a classic motorcycle! But when burglaries and suspicious accidents send the benefit skidding out of control, Frank and Joe find themselves racing to crack another case. As the Hardys make their way through the long list of possible saboteurs, danger gains on them. Can they cut the criminal off before the finish line, or is this race speeding toward disaster?
8-12.
Keywords: Hardy Boys (Fictitious characters) -- Juvenile fiction; Detective and mystery stories; Motocross -- Juvenile fiction; Criminals -- Juvenile fiction; Detective and mystery stories; Mystery fiction; Children's stories